MODEL PEMBELAJARAN PAIKEM PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR: MODEL PEMBELAJARAN PAIKEM PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Rohana, Sy Rohana (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2022)
This journal discusses the learning model in the subject of Islamic Religious Education in Elementary Schools. In the learning process, a model is very important, an Islamic Religious Education teacher in elementary school must be able to adjust the model and learning material. This writing aims to discuss learning models that are in accordance with the material taught by teachers, even though elementary schools generally use thematic learning models which are mandatory in the implementation of learning in all subjects in grades I – IV. The writing method used is library research by looking for books and discussions, theories that are relevant to the problem to be studied. The results of the study of this article show that the PAIKEM learning model is theoretically suitable to be applied in the learning process of Islamic Religious Education in Elementary Schools.